Articulating Design and Pedagogical Needs for Technology-Integrated Folktale-Based English Materials - Widya Rizky Pratiwi; Juhana Juhana; Lukytta Gusti Acfira; Nazirah Binti Md Yusof (Institut Agama Islam Negeri (IAIN) Curup, 2026)
The rapid integration of digital technology in English Language Teaching (ELT) has created new opportunities for learner-centered and culturally responsive instruction; however, speaking skills remain underdeveloped in many English as a Foreign Language (EFL) context. This study addresses this gap by articulating teachers’ design and pedagogical needs for technology-integrated folktale-based English materials, particularly to support speaking skills, learner autonomy, and cultural awareness. Employing a qualitatively driven needs analysis within the Define stage of a Research and Development (R&D) framework, the study involved a questionnaire administered to 38 junior secondary school English teachers, complemented by semi-structured interviews with nine teachers from urban, suburban, and rural contexts. Descriptive statistics were used to identify dominant needs, while thematic analysis provided interpretive depth. The findings reveal five priority needs: technology integration as a core instructional component, reinforcement of cultural values through folktales, speaking models and structured speaking practice, preference for visual and simple design, and the need for adaptation of existing materials. The study highlights that teachers prioritize pedagogically meaningful, user-friendly, and culturally grounded materials over technologically complex systems. These findings contribute theoretical, pedagogical, and methodological insights for developing context-sensitive, speaking-oriented digital English materials grounded in local cultural narratives.